Pengembangan UMKM Berbasis Koptren: Melalui Pendidikan Tinggi, Bank Wakaf Mikro dan Keterampilan Bisnis - Suharto; Muhammad Iqbal Fasa; Ersi Sisdianto (Al-Ulum, 2024)
This study investigates the roles of Higher Education, Micro Waqf Banks, and Business Skills in developing Micro, Small, and Medium Enterprises (MSMEs) within pesantren (Islamic boarding schools). Using a quantitative approach, data were collected via structured questionnaires from MSME entrepreneurs in the pesantren community, analyzed through multiple regression. Results show that Higher Education significantly enhances managerial capabilities, while Micro Waqf Banks provide essential financial support. Business Skills are also crucial for effective management. The research highlights the interconnectedness of education, financial resources, and skill development in fostering entrepreneurship in pesantren. Limitations include a focus on a single geographic area, suggesting future studies should explore diverse regions and long-term impacts on MSME sustainability.